Entre saltos, equilíbrios e rotações: a trajetória de formação e a produção científica de professoras de ginástica do ensino superior - MACIAS, Céres Cemírames de Carvalho (Universidade Federal do Pará, 2017)
The aim of this thesis is to study the training journey and scientific production of gymnastics teachers who work in higher education. I oriented the process of building the research based on the need to understand how the formation journey and the scientific production of graduation gymnastics teachers were composed. In order to do it, I asked: How does the theme about the formation jouney affect the research in education and in physical education? How did the schooling journey of Gymnastics teachers of higher education took place in their graduation in Physical Education? What are the professional paths taken by teachers to achieve their scientific consolidation as researchers in the Physical Education field? How was the scientific production of these university teachers in the physical education field in Brazil? What methodological approaches are identified in the scientific production of these teaching professionals? For answering these questions, I defined as a general objective of the research to analyze the training journey and the scientific production of Gymnastics teachers of higher education. Among the possible paths, I chose to work with the bibliographical and documentary research, the sources were collected in electronic sites and in the Lattes Platform in the curriculum of eight teachers who produced in the field of teacher training in gymnastics, and the information on groups to which they are linked ,Contained in the CNPq Group Directory. The investigation covered the period 1972-2013. The process was based on studies by Corrêa (2012, 2011), Almeida (2012), Gatti (2012), Sánchez Gamboa (2012), Taffarel and Morshbacher (2012), Imbernón (2011), Mészáros ) and Daólio (1998). I conclude that, from the epistemological point of view, although the training journey constitutes the object of study prioritized in educational research, in the scope of Physical Education it is still a rarity or almost nonexistent. However, training at the masters and doctorate levels and joining postgraduate teaching promoted the practice of research among Gymnastics teachers, stimulating their participation in research groups, either as a leader or researcher, which motivated them for scientific production through research projects and texts, that began circulating as books, chapters of books and works in conference annals. Despite this evolution, two types of approaches persist to guide the researchers' scientific practice: empirical-analytical and critical-dialectic. In the midst of this paradigmatic dispute, the themes related to training, education and physical education brought together the greatest number of scientific production, surpassing the field of Gymnastics as an interestamong the teachers themselves involved with the pedagogical work in this field of study.